Administration of Kyung-Ok-Ko reduces stress-induced depressive behaviors in mice through inhibition of inflammation pathway. (30th January 2021) - Liu, Quan Feng; Park, Sun-Woo; Kim, Young-Mi; Song, Sue-jin; Chin, Young-Won; Pak, Sok Cheon; Jeon, Songhee; Koo, Byung-Soo
Abstract: Ethnopharmacological relevance: Kyung-Ok-Ko (KOK), a traditional medicinal formula composed of Rehmannia glutinosa (Gaertn.) DC, Poria cocos (Schw.) Wolf, Korean Red Panax ginseng C.A.Mey, and honey, has been used to treat amnesia and dementia. KOK has also been shown to ameliorate transient cerebral global ischemia-induced brain damage, but the antidepressant-like effect of KOK has not been examined. Aim of the study: This study examined the antidepressant-like effect of KOK in an immobilization-induced stress mouse and its mechanisms of action. Materials and methods: The animals in the stress group were immobilized for two hours a day for two weeks. KOK at a dose of 1 g/kg/day was administered orally to the stressed mice for two weeks in advance of their immobilization. A forced swimming test was performed to analyze their depressive behaviors. To examine the anti-inflammatory or antioxidative effects of KOK, the murine macrophage cell line, RAW 264.7 cells and human neuroblastoma cell, SH-SY5Y cells, were treated with lipopolysaccharide (LPS) and hydrogen peroxide, respectively. Result: The KOK extract showed no significant toxicity when the cells were treated with a KOK extract at 5, 10, 25, 50, and 100 μg/mL. The KOK ethanol extract reduced LPS-induced TNF-α production, inducible nitric oxide (iNOS) mRNA level, and the levels of MAPK and p38 phosphorylation in RAW 264.7 cells. KOK also suppressed H2 O2 -induced cell death and the production of reactive oxygen species (ROS) in SH-SY5Y cells. In the forced swimming test, KOK induced a decrease in immobility and an increase in climbing activity. Finally, the administration of KOK reversed the up-regulation of IkB-α phosphorylation in the stressed mouse cortex. Conclusion: KOK might be useful for the treatment of depression caused by environmental and lifestyle-related stress. Graphical abstract: Image 1